A 3D hydrodynamic simulation of a black hole outflow in a dwarf spheroidal galaxy. Issue Volume 14:Issue S344(2019) (August 2018) - Lanfranchi, Gustavo A.; Caproni, Anderson; Hazenfratz, Roberto
Abstract: We present results from a non-cosmological, three-dimensional hydrodynamic simulation of an outflow from an intermediate-mass black hole in Dwarf Spheroidal Galaxies. Assuming an initial baryonic-to-dark-matter ratio derived from the CMB radiation and a cored, static dark matter potential, we evolved the galactic gas distribution over 3 Gyr, taking into account the outflow of a black hole. Our results indicate that in a homogeneous medium the outflow propagates freely in both directions with the same velocity and its capable of removing a fraction of the gas from the galaxy (it depends on the initial conditions of the outflow). When the SNe are taken into account, the effect of the outflow is substantially reduced. It is necessary an initial velocity around 1000 km/s and a density larger than 0.003 particles.cm −3 for the outflow to propagate. In these conditions, the removal of gas from the galaxy is almost negligible at the end of the 3 Gyr of the simulation.